DISASTER MITIGATION AND THE ROLE OF LOCAL WISDOM THROUGH THE PALU-KORO Fault and the LEMBANG Fault - Vania Qanita Damayanti (Universitas Pendidikan Indonesia, 2021)
This study describes the Palu-koro fault and the Lembang fault in relation to messages that have existed since ancient times. This message is in the form of a topomini that warns about disaster mitigation in areas that are prohibited from being inhabited. The message of the past is local wisdom as a consideration in making policies along with the results of research by experts. The purpose of this study is to reveal the message of local wisdom that is stored behind works of art and literature and then made a documentary film as a media for mitigating literacy for the people of Indonesia. This study uses a qualitative method with a descriptive analysis approach. Data obtained through observation, interviews, documentation and literature study. The results of this study can summarize the events that have happened to the city of Palu due to the Koro hammer fault movement which then created an earthquake and tsunami and claimed a large number of victims. Art and literature can be collected again as messages from the past for media literacy for today's modern society. The implication of this research should be one of the findings that can oversee government policy in granting building permits in disaster-prone areas. Disaster mitigation should also be carried out by involving local wisdom as the main source in analyzing policies.